RELIGION AND POLITICS: THE INDIAN SCENARIO - Panthaplemthottiyil, Jose (Journal of Dharma, 2000)
Indiahas often been described as the land of religions. Indeed, not only are all the major religions of the world found here to be existing triumphantly for thousands of years, but more importantly, all the religions continue to have significant influence on the lives of their adherents ID! both cult and view of life. In consequence, religion has been a major factor in socio-political identity as also in social cleavage both independently of and in association with language and caste in India.